The Impact of Waste Management Practice Initiatives on the Sustainability of commercial banks in Sri Lanka - Serasinghe, M.; De Silva, P.; Gunaratne, C. (NSBM Green University, 2022)
One of the major issues confronting the banking sector is a lack of knowledge and awareness about waste management and sustainability. Herein, the social, economic, environmental and philanthropic responsibility falls on the shoulders of top management, who is responsible for managing business practices including waste management practices by fostering trust and effective communication. As a result of globalization, digitalization, and the Covid -19 pandemic period, waste minimization and sustainability have been significant banking and finance constructs in recent years, notably in relationship management in the service industry. Therefore, this research is conducted to examine the impact of Waste Management Practice Initiatives on the Sustainability of commercial banks in Sri Lanka. This study has been conducted using Legitimacy Theory. The research is conducted under the quantitative method where data from 370 respondents (Management Level employees of the Commercial Banks in Colombo District) were collected through Emails and WhatsApp by a Google questionnaire. The data analysis was conducted through SmartPLS 3.0 and SPSS 25 software. The key research finding is that there is a positive association between Waste Management Practice Initiatives and Commercial Bank Sustainability in Sri Lanka. The main research limitations are that the sample is limited to the Colombo District and that the survey was conducted online only with managerial-level personnel. Future studies should broaden the sample and focus more on mixed method and qualitative methodologies with middle and operational level staff. In terms of managerial impact, top managers, commercial banks, employees, and the government would be beneficial. Future studies could examine further supporting virtues for the Legitimacy Theory as well as other useful considerations for future mechanisms to promote waste management practice initiatives, which would increase Commercial Banks' long-term sustainability.